Arthrocentesis for the Treatment of Internal Derangement of the Temporomandibular Joint - Neeli, Arati S. (Springer-Verlag, 2011)
OBJECTIVE: The study aims to evaluate the efficacy of arthrocentesis in the treatment of internal derangement of the temporomandibular joint (TMJ). STUDY DESIGN: Thirty patients with TMJ internal derangement underwent arthrocentesis using saline. Pain using visual analog scale, maximum mouth opening, joint noises and mandible deviation were documented pre-operatively and post-operatively. Patients were followed for 1 year. Statistical analysis of pain was done by Wilcoxon signed Rank’s test and dysfunction by students paired t test. RESULTS: The mean pre-operative pain was 4.8 ± 2.65 and post-operatively at 1 year was 0.27 ± 0.45 with an average decrease of 4.72 (P = 0.000). The mean maximal mouth opening pre-operatively was 29.8 ± 2.35 mm and post-operatively 41.9 ± 2.48 mm at 1 year. The mean increase in the mouth opening was 12.1 ± 3.0 mm (P = 0.000). CONCLUSION: Arthrocentesis is simple, minimally invasive procedure with less risk of complications and significant benefits in patients with TMJ internal derangement.